Vpliv objedanja zaradi rastlinojede divjadi na gostoto in višinsko preraščanje gozdnega mladja na Tolminskem gozdnogospodarskem območju - Koren, Iztok (Gozdarski vestnik, 2025)
In the Tolmin forest management area, we determined the dynamics of the abundance of forest young trees and how they grow in height during the three inventories in the years 2016, 2020 and 2024 on the same 114 plots. The frequency structure of the number of saplings changed significantly over the course of the three inventories, both in total and between groups of tree species and between groups of forest management units. The number of young trees decreased over the course of the three inventories; it also decreased within the first and second height classes, while within the next three height classes the number of young trees increased. The decrease or increase in the number of young trees within height classes during the three inventories varies by tree species groups, and varies by groups of forest management units, where the differences are smaller. We found a negative relationship between the level of grazing and height overgrowth. The least eaten are spruce and beech, which also grow the best in height. As grazing increases, the number of young trees decreases in all height classes.
Keywords: forest young trees; gozdno mladje; grazing by herbivores; heigh classes; heigh overgrowth; objedanje zaradi rastlinojedov; Tolmin forest management area; Tolminsko gozdnogospodarsko območje; višinski razredi; višinsko preraščanje